Acute effects of a robotic ankle exosuit on the gait biomechanics, metabolic cost, and muscle activity during walking in patients with unilateral cerebral palsy - Thurston, Maxwell (2021)
The ability to walk is important for mobility, community participation, and independence. However, for patients with Cerebral Palsy (CP), walking can be impaired due to these patients’ neuromuscular and musculoskeletal limitations. The neural lesion that underlies CP leads to various motor impairments, such as muscle weakness, deficient motor control, and reduced joint range of motion, which can all inhibit patient’s walking capacity. Current treatments for CP mostly focus on correcting or improving specific musculoskeletal deficiencies, but are commonly ineffective at improving patients’ overall walking ability. New clinical technologies, such as exoskeletons and exosuits may enable enhanced gait therapy for patients with neuromotor dysfunction, such as those with CP. The early evidence using these devices in patients with motor impairments has been highly positive, showing improvements in biomechanics, muscle activity, and energy cost during robotically augmented walking. However, very little research has investigated the use of these devices in patients with CP. The purpose of this thesis was to investigate the acute effects of a robotic ankle exosuit on the gait biomechanics, muscle activity, and metabolic cost during walking in a small cohort of adolescents and young adults with unilateral CP. Seven participants with unilateral CP (12-16 years old, GMFCS I) were recruited for this study. The protocol involved walking on a force-sensing treadmill while 3D motion capture, surface electromyography, and oxygen consumption were used to measure lower limb gait kinematics and kinetics, muscle activity, and metabolic cost. Three walking trials were performed: 1) normal walking without the exosuit, 2) walking with the exosuit while carrying the device’s motor (onboard), and 3) walking with the exosuit with the motor offloaded from the body (offboard). The exosuit used in this study assists plantarflexion and dorsiflexion movements of the patient’s affected ankle joint during walking via contractile cables at the front and rear of the foot. The results showed that the exosuit improved affected ankle mechanics (improved dorsiflexion at ground contact (*onboard: +9.98° [p=0.002], *offboard: +9.20° [p=0.004]) and increased peak plantarflexor moment at push-off (*onboard: +0.09 Nm/kg [p=0.037], offboard: +0.11 Nm/kg)) and amplified positive power generation at the knee in the unaffected leg (*onboard: +0.28 W/kg [p=0.041], *offboard: +0.19 W/kg [p=0.011]), as well as produced a trend towards generally reduced muscle activity across the lower limb muscles. These biomechanical and muscle activity changes likely contributed to the reduced metabolic cost observed while walking with the exosuit, especially in the offboard condition (onboard: -6.9%, offboard: -14.7%), however this reduction was not statistically significant. These results point to the potential of this exosuit, as well as similar robotic assistive technology, to augment walking mechanics, energetics, and muscle activity, and thus support future research with these devices to improve mobility in patients with CP.